2010
DOI: 10.1146/annurev.biophys.050708.133652
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring Cells: Synthetic Biology as a Tool to Interrogate the Organizational Principles of Living Systems

Abstract: The living cell is an incredibly complex entity, and the goal of predictively and quantitatively understanding its function is one of the next great challenges in biology. Much of what we know about the cell concerns its constituent parts, but to a great extent, we have yet to decode how these parts are organized to yield complex physiological function. Classically, we have learned about the organization of cellular networks by perturbing them through genetic or chemical means. The emerging discipline of synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
161
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(163 citation statements)
references
References 77 publications
2
161
0
Order By: Relevance
“…Second, the approach is generic and could be extended to other signalling proteins, such as kinases, that exhibit non-trivial behaviours when they work collectively or are recruited by scaffolding proteins 39 . Finally, from a synthetic biology perspective, there is mounting interest regarding the engineering of essential functions such as switches and oscillators 13,40,41 . Our approach provides a bottom-up strategy using the magnetic actuation of ultrasensitive responses of GTPase proteins, which act as molecular switches.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the approach is generic and could be extended to other signalling proteins, such as kinases, that exhibit non-trivial behaviours when they work collectively or are recruited by scaffolding proteins 39 . Finally, from a synthetic biology perspective, there is mounting interest regarding the engineering of essential functions such as switches and oscillators 13,40,41 . Our approach provides a bottom-up strategy using the magnetic actuation of ultrasensitive responses of GTPase proteins, which act as molecular switches.…”
Section: Discussionmentioning
confidence: 99%
“…One important implication of our results is inference of some genome design principles (2,4). In particular, we studied the rewired TRNs that had achieved over-optimality or lost optimality.…”
Section: Discussionmentioning
confidence: 99%
“…Isalan et al (3) added transcriptional fusions of promoters with different master transcriptional regulators and showed that Escherichia coli (E. coli) tolerated almost all rewired networks; however, growth was perturbed by as much as 5% (3). This inherent predisposition of E. coli networks to dampen extreme changes in their circuitry enables the possibility of conducting genome-wide rewiring (4). Global transcription regulation could also be analyzed by comparing the regulatory models from distant organisms, provided they show a similar response to the set of studied environments.…”
mentioning
confidence: 99%
“…Despite the complexity of the task, during the last decade there have been significant advances in building synthetic biochemical oscillators, some of them towards replicating the inherent robustness of natural systems (Purcell et al 2010;Bashor et al 2010;Toettcher et al 2010;Kim and Winfree 2011). Synthetic functional circuits incorporating oscillators as time-keepers have also been developed (Danino et al 2010;Mondragon-Palomino et al 2011;Franco et al 2011;Khalil and Collins 2014).…”
Section: Introductionmentioning
confidence: 99%